Analysis of Elastic Wave Characteristics for Solid-State Medium Propagation under Rotation - Durukan, Yasemin; Peregudov, Aleksander N.; Popkova, Ekaterina S.; Shevelko, Michail M. (2019 International Conference "Quality Management, Transport and Information Security, Information Technologies" (IT&QM&IS), 2019)
The analysis of bulk acoustic wave characteristics when propagating into rotating elastic solid-state medium is provided. Two special cases for coaxial and orthogonal relative orientation of wave propagation and medium rotation directions are considered. For these two cases the wave polarization types and phase velocities are found. The bulk acoustic wave properties that can be the base of gyro sensitive element operation are determined.